Dronningens mønt; Om penge, rang og distinktioner - Liep, John (Tidsskriftet Antropologi, 2004)
The article introduces the phenomenon of ranked money by a description of the ndap system of shell money on Rossel Island, Papua New Guinea. This money is divided in many classes from rare, named and sacred objects in the upper part of the system down to common low-value pieces towards the bottom. It is shown that high-ranking shells are more like decorations or tokens of authority while low-ranking ones are more similar to our money. Further, payment displays of shell money index the social precedence of participants in transactions. Similar cases of ranked money in the Pacific are presented. Relevant theory by Graeber, Hart, Kopytoff and Annette Weiner is reviewed to elucidate the phenomenon. I then turn to two public Danish value objectifications: state money and the royal system of regalia, orders and medals. I show how in our modern society a split has appeared between money as a commercial medium and royal distinctions as tokens of honour in an alternative hierarchical domain of value. There is, however, a “missing link”: at great occasions in the royal family special large commemorative coins of silver are issued. One of these is placed as a royal gift with each cover at the banquet celebrating the event.